A facility maintenance scheduling model incorporating opportunity and inflationary costs (2008)
This paper deals with facility maintenance scheduling model which incorporates opportunity and inflationary cost. A case study pertaining to a shipping firm has been defined as transportation model of minimizing Maintenance Cost (MC), Maintenance –Inflation Cost (MIC), Maintenance-Opportunity Cost (MOC) and combined Maintenance-Opportunity-Inflation Cost (MOIC), The optimal schedules indicating the ship maintenance, idle and operation periods were deduced for each approach. For all the samples, the costs of the first model were significantly (p≤0.05) different from that of the other three models. To reduce cost and delays, decisions for scheduling maintenance of a fleet of ships would be better informed if based on maintenance and opportunity cost indices in both inflationary and non-inflationary conditions.